2014
DOI: 10.1021/jp501941b
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Hydroformylation Catalyzed by RhH(CO)2[(R,S)-Yanphos]: Mechanism and Origin of Enantioselectivity

Abstract: Asymmetric hydroformylation (AHF) catalyzed by transition metal (TM) complexes bearing chiral phosphorus ligands is one of the most powerful synthetic ways that could provide chiral aldehydes directly from alkenes and syngas in one step. Experiments have proved the efficiency of Rh catalyst with hybrid phosphorus ligands owning two different phosphorus moieties in AHF. Herein the origin of enantioselectivity of AHF catalyzed by RhH(CO)2[(R,S)-Yanphos] was studied at M06/BSI level using the density functional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…As shown in Fig. 5 , the alkene insertion step was computed to be the rate-determining step, which is in agreement with the previous computational studies 51 56 and no observation of the H/D scrambling from the product (Fig. 7 ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As shown in Fig. 5 , the alkene insertion step was computed to be the rate-determining step, which is in agreement with the previous computational studies 51 56 and no observation of the H/D scrambling from the product (Fig. 7 ).…”
Section: Resultssupporting
confidence: 89%
“…On the basis of the previous computational and experimental results on other Rh-catalyzed hydroformylation 8 , 51 – 57 , we also carried out DFT calculations (using ( S , R )-( N -Bn)-YanPhos and 1a ) to examine energetics of the whole reaction path for this Rh-catalyzed AHF and understand its regioselectivity and enantioselectivity to gain more insightful understanding (Figs. 5 and 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…[29][30][31][32][33][34][35][36][37][38][39] The hybrid density functional ωB97X-D method is reliable and has been used in previous studies. [40][41][42] The transition states (TSs) were further confirmed by the vibrational analysis and characterized by only one imaginary vibrational mode. The intrinsic reaction coordinate (IRC) calculations were performed in order to confirm and identify intermediates (INTs) along the reaction pathways.…”
Section: Computational Detailsmentioning
confidence: 87%
“…For instance, QM/MM computations have been employed to gather qualitative as well as quantitative estimates on the origin of enantioselectivity in catalytic AHF reactions in the recent years. The DFT (M06) studies using simplified models for Rh-YanPhos catalyst suggested that the efficiency of alkene coordination is an important factor that has a bearing on the enantioselectivity . It is important to note that the stereochemical outcome of asymmetric transformations could depend on the catalyst–substrate noncovalent interactions (NCIs) .…”
Section: Introductionmentioning
confidence: 99%
“…The DFT (M06) studies using simplified models for Rh-YanPhos catalyst suggested that the efficiency of alkene coordination is an important factor that has a bearing on the enantioselectivity. 25 It is important to note that the stereochemical outcome of asymmetric transformations could depend on the catalyst− substrate noncovalent interactions (NCIs). 26 Therefore, the use of QM/MM approaches that typically place the regions of the ligand in the MM framework is likely to be ineffective.…”
Section: ■ Introductionmentioning
confidence: 99%